BOVINE SERUM ALBUMIN DENATURATION IN THE PRESENCE OF HOECHST 33258 AND METHYLENE BLUE (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The interaction of Hoechst 33258 (H33258) and methylene blue (MB) compounds with bovine serum albumin (BSA) has been studied using the method of thermal denaturation. The obtained data showed that both ligands form complexes with BSA, moreover, MB binds to BSA stronger than H33258. Furthermore, H33258 destabilizes, while MB stabilizes the native structure of protein, leading to the decrease and increase of the denaturation temperature of BSA respectively.
Keywords: bovine serum albumin; methylene blue; Hoechst 33258; interaction; denaturation temperature